Characterization of mechanical properties of high density polyethylene matrix composites reinforced with natural fibers for application in safety footwear toe caps. - Guzmán Sánchez, Manuel Alberto
Safety footwear has become a vitally important aspect in manufacturing industries to protect feet from potential risks such as heavy objects, impact, cuts, penetration and compression, and other potential risks such as chemical, thermal, and electrical. Composite materials are used to obtain a combination of properties that cannot be achieved any other way; and thus achieve unusual combinations of rigidity, weight, density, high-temperature performance, corrosion resistance, hardness, or conductivity. In this study, high-density polyethylene (HDPE) matrix composite materials reinforced with natural fique, pineapple, and banana fibers were used for application in safety footwear toe caps. The results show that the pineapple fiber provides mechanical properties such as tensile strength, Young's modulus, and bending resistance that are similar or high compared to the virgin material and the other fibers. Additionally, compression and impact tests were carried out on prototypes of toe caps reinforced with natural fibers following the specifications of international quality standards.